Renal tubular dysgenesia at the Pereira Rossell Children Hospital (Archives of Pediatrics of Uruguay, 2020)
Renal tubular dysgenesis is an acquired or inherited autosomal recessive disease. Before birth, it shows as oligohydramnios resulting from fetal anuria and after birth, it shows as persistent anuria, pulmonary hypoplasia, severe refractory hypotension and alteration of the ossification of the cranial bones. Histologically, it is an alteration of the development of the renal tubules. We hereby introduce a clinical case of a newborn who presented renal failure, multiple dysmorphia and pulmonary hypoplasia at birth, who died at 3 days of age and whose autopsy showed renal tubular dysgenesis.
Keywords: Congenital abnormalities; Renal tubules; Oligohydramnios; Renal Insufficiency; Newborn